2020
DOI: 10.3390/ph14010014
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Delivery Systems for Peptide Nucleic Acids

Abstract: The number of applications of peptide nucleic acids (PNAs)—oligonucleotide analogs with a polyamide backbone—is continuously increasing in both in vitro and cellular systems and, parallel to this, delivery systems able to bring PNAs to their targets have been developed. This review is intended to give to the readers an overview on the available carriers for these oligonucleotide mimics, with a particular emphasis on newly developed multi-component- and multifunctional vehicles which boosted PNA research in rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 238 publications
(306 reference statements)
0
22
0
Order By: Relevance
“…This strategy allows the uptake of the majority of the PNA molecules within few hours, reaching a maximum level (near 100%) after 72 h, as firstly published by Brognara et al [ 58 ] and then confirmed by several studies of our group [ 38 , 39 , 46 , 50 ]. The issue of PNA delivery has been fully addressed in a recent review paper by Volpi et al [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…This strategy allows the uptake of the majority of the PNA molecules within few hours, reaching a maximum level (near 100%) after 72 h, as firstly published by Brognara et al [ 58 ] and then confirmed by several studies of our group [ 38 , 39 , 46 , 50 ]. The issue of PNA delivery has been fully addressed in a recent review paper by Volpi et al [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…While these delivery methods and related recent findings will not be discussed in detail in this review, the readers can refer to comprehensive overviews of these PNA delivery mechanisms elsewhere. [ 100,103 ]…”
Section: Delivery Of Pnamentioning
confidence: 99%
“…Furthermore, the precise control of gene knockdown provided by siRNA has allowed researchers to delineate important relationships between EWS/FLI and downstream targets such as MYC, IGFBP3, NR0B1, STEAP1, CALCB, and several neural crest specific genes [72] , [75] , [76] , [77] , [78] , [79] . The creation of nanoparticles containing these targeted oligonucleotides remains an ongoing area of investigation [80] , [81] . In addition, one such construct is currently being evaluated in the clinic (NCT02736565).…”
Section: Oligonucleotide Based Approaches Targeting Ews/flimentioning
confidence: 99%